Pengaruh Kompetensi, Profesionalisme, dan Disiplin Kerja Terhadap Promosi Jabatan Pada PT. Dharma Intisawit Lestari (DIL) di Kecamatan Tanjung Palas Timur - Riani R; Dedik Wiryawan; Hermawan H (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Influence of Competence, Professionalism and Work Discipline on Job Promotion at Pt. Dharma Intisawit Lestari (DIL) in East Tanjung Palas District, Management Study Program Thesis, Faculty of Economics, University of North Kalimantan. Supervised by Mr. Dedik Wiryawan S.T, M.M. This study aims to determine competence, professionalism and work discipline regarding promotion at Pt. Dharma Intisawit Lestari. The type of research used in this research is quantitative. The population in this study were all employees at PT. Dharma Intisawit Lestari, numbering 38 people. The results of this study indicate that it is known that the significance value for the influence of variable X1 on variable Y is equal to 0.071 > 0.05 and the value of t count is 1.865 t table 2.032 so it can be concluded that H1 is rejected which means that there is no effect of variable X1 on variable Y. Effect of variable X2 to variable Y is 0.041 0.05 and the t count is 2.122 > t table 2.032 so it can be concluded that H2 is accepted, which means that there is an influence of variable X2 on variable Y. The effect of variable X1 on variable Y is 0.441 > 0.05 and the value of t calculated 0.833 t table 2.032 so it can be concluded that H3 is rejected, which means there is no influence of Variable X3 on variable Y.